Accelerators for achieving the sustainable development goals in Sub-Saharan-African children and young adolescents – A longitudinal study. (March 2022) - Haag, Katharina; Du Toit, Stefani; Rudgard, William E.; Skeen, Sarah; Meinck, Franziska; Gordon, Sarah L.; Mebrahtu, Helen; Roberts, Kathryn J.; Cluver, Lucie; Tomlinson, Mark; Sherr, Lorraine
Highlights: Living in a safe community, attending community-based organisations, food security and being in receipt of caregiver monitoring and praise showed accelerating effects for numerous outcomes related to the sustainable development goals. Additive effects for combined interventions were relatively robust for mental health outcomes; school-factors require further research. Existing interventions could be utilised or new ones devised to improve accelerator access. Community-based organisations may be well-placed to deliver accelerating services to those most vulnerable.